Biosynthesis of Hybrid Neutral Lipids with Archaeal and Eukaryotic Characteristics in Engineered Saccharomyces cerevisiae. (14th December 2022) - Zhang, Jianzhi; Li, Tuo; Hong, Zhilai; Ma, Chenfei; Fang, Xiaoting; Zheng, Fengfeng; Teng, Wenkai; Zhang, Chuanlun; Si, Tong
Abstract: Discovery of the Asgard superphylum of archaea provides new evidence supporting the two‐domain model of life: eukaryotes originated from an Asgard‐related archaeon that engulfed a bacterial endosymbiont. However, how eukaryotes acquired bacterial‐like membrane lipids with a sn ‐glycerol‐3‐phosphate (G3P) backbone instead of the archaeal‐like sn ‐glycerol‐1‐phosphate (G1P) backbone remains unknown. In this study, we reconstituted archaeal lipid production in Saccharomyces cerevisiae by expressing unsaturated archaeol‐synthesizing enzymes. Using Golden Gate cloning for pathway assembly, modular gene replacement was performed, revealing the potential biosynthesis of both G1P‐ and G3P‐based unsaturated archaeol by uncultured Asgard archaea. Unexpectedly, hybrid neutral lipids containing both archaeal isoprenoids and eukaryotic fatty acids were observed in recombinant S. cerevisiae . The ability of yeast and archaeal diacylglycerol acyltransferases to synthesize such hybrid lipids was demonstrated. Abstract : Reconstitution of archaeal lipid biosynthesis in eukaryotic Saccharomyces cerevisiae resulted in unexpected production of hybrid neutral lipids, which contain both archaeal isoprenoids and eukaryotic fatty acids. The responsible enzymes, diacylglycerol acyltransferases (DGATs), were found to be present in all domains of life.